2016
DOI: 10.3346/jkms.2016.31.9.1479
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Sarcopenia in Korean Patients after Hip Fracture: a Case-Control Study

Abstract: Sarcopenia-related falls and fractures are increasing worldwide due to the aging population. The purpose of this study was to 1) evaluate anthropometric characteristics related to hip fracture in Korean patients, 2) investigate sarcopenia prevalence in hip fracture (HF) and non-hip fracture (NF) groups, and 3) investigate the correlation between sarcopenia and osteoporosis. This case-control study examined 359 HF and 1,614 NF normal populations using Korea National Health and Nutrition Examination Survey data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 19 publications
4
49
0
1
Order By: Relevance
“…Review of the titles and abstracts yielded 241 relevant studies for full‐text screening. Thirty‐six studies met all inclusion criteria and were included in this review . A total of 33 studies were included in the meta‐analysis; four of them presented data for both falls and fractures, leaving 20 studies included in the meta‐analysis for falls and 17 studies for fractures …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Review of the titles and abstracts yielded 241 relevant studies for full‐text screening. Thirty‐six studies met all inclusion criteria and were included in this review . A total of 33 studies were included in the meta‐analysis; four of them presented data for both falls and fractures, leaving 20 studies included in the meta‐analysis for falls and 17 studies for fractures …”
Section: Resultsmentioning
confidence: 99%
“…Study populations included community‐dwelling individuals (22 studies), hospitalized patients (3 studies), outpatients (4 studies), and nursing home residents (3 studies) . Four studies included a combined group of hospitalized patients with fractures and community‐dwelling individuals without fractures . Two studies reported retrospective data, 20 studies were cross‐sectional, 13 studies were prospective, and 1 study was a randomized controlled trial examining the effect of nutritional supplementation on bone mineral density and risk of falls .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) It is an indicator of overall muscular strength, nutritional status, muscle mass, and walking performance (234). Recently, HGS has been used as important index of low muscle strength to diagnose sarcopenia because low HGS is a clinical marker of poor mobility and a better predictor of clinical outcome of low muscle mass (567). According to guideline for European working group on sarcopenia in older people (EWGSOP, the Sarcopenia Working Group), low muscle strength using cut-off point for HGS at two standard deviations below the mean reference value is defined as < 30 kg in men and < 20 kg in women.…”
Section: Introductionmentioning
confidence: 99%